Engineering rice Nramp5 modifies cadmium and manganese uptake selectivity using yeast assay system - Inoue, Junji; Teramoto, Takamasa; Kazama, Tomohiko; Nakamura, Takahiro (Frontiers in Plant Science, 2024)
Cd is a seriously hazardous heavy metal for both plants and humans and international regulations regarding Cd intake have become stricter in recent years. Three-quarters of the Cd intake comes from plant-based foods, half of which comes from cereals. Therefore, it is anticipated that the Cd uptake efficiency of cereals, including rice, a staple crop in Asia, will be reduced. Natural resistance-associated macrophage protein (Nramp) is the principal transporter involved in the uptake and translocation of metal ions in various plants. In rice, OsNramp5 is a transporter of Mn, which is an essential micronutrient for plant growth, and is responsible for Cd uptake. Although several attempts have been made to engineer the metal uptake characteristics of OsNramp5, in many cases, both Cd and Mn uptake efficiencies are impaired. Therefore, in this study, we engineered OsNramp5 to reduce Cd uptake while retaining Mn uptake efficiency for low-Cd rice production. OsNramp5 was engineered using amino acid substitution(s) at the 232 nd Ala and 235 th Met of OsNramp5, which have been suggested to be key residues for metal uptake efficiency and/or selectivity by structural analyses of bacterial Nramps. The metal uptake efficiency was first analyzed using a yeast model assay system. Several mutants showed less than 8.6% Cd and more than 64.1% Mn uptake efficiency compared to the original OsNramp5. The improved metal uptake characteristics were confirmed by direct measurement of the metal content in the yeast using inductively coupled plasma optical emission spectroscopy. Notably, several mutants reduced Cd uptake efficiency to the background level while retaining more than 64.7% Mn uptake efficiency under conditions mimicking heavily polluted soils in the world. In addition, computational structural modeling suggested requirements for the spatial and chemical properties of the metal transport tunnel and metal-binding site, respectively, for Cd/Mn uptake efficiency.